A psychological contract perspective of vertical and distributed leadership in project-based organizations. Issue 3 (April 2021) - Agarwal, Upasna A; Dixit, Vijaya; Nikolova, Natalia; Jain, Karuna; Sankaran, Shankar
Highlights: There was prevalence of distributed leadership inIndian and Australia project-based organizations. Operational and technical aspects were taken by project team and managers while strategic decisions were made by senior management. Organizational culture, knowledge sharing, and project management practices influenced leadership style. Leadership styles impact the state of psychological contract (fulfilment/breach). Abstract: The primary purpose of this study is to examine the relationship between two leadership styles (vertical and distributed), conceptualized through types of decisions made (strategic and operational/tactical), and the state of psychological contract (fulfillment/breach) at three different levels of the organizational hierarchy in project-based organizations. The explorative analysis of eight organizations from India and Australia demonstrates the prevalence of distributed leadership: operational and technical decisions are usually entrusted to the project team and project managers, while strategic decisions are made by senior management. The study suggests that three factors facilitate a specific leadership style (vertical or distributed): organizational culture, knowledge sharing and project management practices, which in turn impact the state of psychological contract (fulfillment/breach). A flexible, collaborative organizational culture supports knowledge sharing and the adoption of agile methods, enabling distributed leadership and leading to psychological contract fulfillment.